Bimetallic and plasmonic Ag and Cu integrated TiO2 thin films for enhanced solar hydrogen production in direct sunlight - Mani, Sunesh S.; Rajendran, Sivaraj; Arun, Pushkaran S.; Vijaykumar, Aparna; Mathew, Thomas; Gopinath, Chinnakonda S. (Energy Advances, 2024)
<div class="abstract author" id="aep-abstract-id7" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Plasmonic metal nanoparticle-integrated mesoporous TiO2 nanocomposites (Ag/TiO2, Cu/TiO2 and Ag–Cu/TiO2), prepared by a simple chemical reduction method, have been demonstrated to show superior activity in thin-film form for solar H2 generation in sunlight. Integration of Ag + Cu on TiO2 significantly enhances the solar H2 production due to the combined SPR effect of both metal species and the possible synergistic interaction among Cu + Ag in Ag–Cu/TiO2. TiAgCu-1 (0.75 wt% Ag and 0.25 wt% Cu on TiO2) showed the highest H2 yield of 6.67 mmol h−1 g−1 and it is 43 times higher than that of bare TiO2. The thin-film form of TiAgCu-1 shows 5 times higher solar H2 production than its powder counterpart. 1 wt% of Ag or Cu on TiO2 shows a H2 yield of 4.6 or 2 mmol h−1 g−1, respectively, which underscores the importance of combined or synergistic effects. The increase in solar H2 generation in Ag–Cu/TiO2 is attributed to factors such as the SPR effect of Cu and Ag, and strong interaction between Ag and Cu. The high photocatalytic efficiency of the TiAgCu-1 thin film is attributed to the large dispersion of metallic species with relatively high Ag/Cu surface atomic ratio, enhanced light absorption, a heterogeneous distribution of Ag and Cu species, and high double layer capacitance. The inter particle mesoporous network increases the interfacial charge transfer and reduces the mass transfer limitations. The plausible photocatalytic reaction mechanism could involve the combination of direct electron transfer from metal (Cu/Ag) to TiO2 as well as the significant field effect due to the Ag–Cu alloy, which is expected to increase the electron excitation locally. <div class="abstract graphical" id="aep-abstract-id9" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Plasmonic metal nanoparticle integrated mesoporous TiO2 nanocomposites (Ag/TiO2, Cu/TiO2 and Ag–Cu/TiO2), prepared by a simple chemical reduction method, have been demonstrated to show superior activity in thin-film form for solar H2 generation.